2004
DOI: 10.1007/978-3-540-30550-7_26
|View full text |Cite
|
Sign up to set email alerts
|

Decidability and Complexity in Automatic Monoids

Abstract: Several complexity and decidability results for automatic monoids are shown: (i) there exists an automatic monoid with a P-complete word problem, (ii) there exists an automatic monoid such that the first-order theory of the corresponding Cayley-graph is not elementary decidable, and (iii) there exists an automatic monoid such that reachability in the corresponding Cayley-graph is undecidable. Moreover, it is shown that for every hyperbolic group the word problem belongs to LOGCFL, which improves a result of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(34 reference statements)
2
8
0
Order By: Relevance
“…Our proof is a variation of a well-known technique for encoding a Turing machine into a string-rewriting system (see, for example, [21]). Our result improves upon a recent result of Lohrey [19], who used a similar method to show that right-reachability for automatic monoids is, in general, undecidable. We use without further comment a number of standard results from the theory of string-rewriting; these can be found in [2].…”
Section: Undecidability Of the Existence Of A Right Inversesupporting
confidence: 90%
See 1 more Smart Citation
“…Our proof is a variation of a well-known technique for encoding a Turing machine into a string-rewriting system (see, for example, [21]). Our result improves upon a recent result of Lohrey [19], who used a similar method to show that right-reachability for automatic monoids is, in general, undecidable. We use without further comment a number of standard results from the theory of string-rewriting; these can be found in [2].…”
Section: Undecidability Of the Existence Of A Right Inversesupporting
confidence: 90%
“…A number of authors have considered decision problems in automatic semigroups; for example, it has been established that the word problem for an automatic semigroup is always decidable in quadratic time [5] and in certain cases is P-complete [19]. In general, this research has assumed a fixed semigroup with automatic structure, and asked what computations can be performed in the semigroup.…”
Section: Introductionmentioning
confidence: 99%
“…LogCFL has several alternative characterizations, see Section 4 for details. The LogCFL upper bound for knapsack in hyperbolic groups improves the polynomial upper bound shown in [22], and also generalizes a result from [16], stating that the word problem for a hyperbolic group is in LogCFL. For hyperbolic groups that contain a copy of a non-abelian free group (such hyperbolic groups are called non-elementary) it follows from [19] that knapsack is LogCFLcomplete.…”
Section: Introductionsupporting
confidence: 70%
“…Let G be a hyperbolic group. In [16] it is shown that the word problem for G is a growing context-sensitive language, i.e., it can be generated by a grammar where all productions are strictly length-increasing (except for the start production S → ε). In [1] it was shown that every growing context-sensitive language can be recognized by a one-way AuxPDA in logarithmic space and polynomial time.…”
Section: The Complexity Class Logcflmentioning
confidence: 99%
“…More recently, this notion has been extended to semigroups [29,30,84,28] and monoids [83,129,102] and has subsequently caught considerable attention.…”
Section: Automatic Groupsmentioning
confidence: 99%